Public debt sustainability international perspectives - Poulson, Barry Warren, 1937-; Merrifield, John, 1955-; Hanke, Steve H. (Lexington Books, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2022)
"This book examines the issue of debt sustainability from an international perspective, with reference to European countries, emerging nations, and the United States"--